2018
DOI: 10.3389/fmars.2018.00101
|View full text |Cite
|
Sign up to set email alerts
|

Corals and Their Microbiomes Are Differentially Affected by Exposure to Elevated Nutrients and a Natural Thermal Anomaly

Abstract: Nutrient pollution can increase the prevalence and severity of coral disease and bleaching in ambient temperature conditions or during experimental thermal challenge. However, there have been few opportunities to study the effects of nutrient pollution during natural thermal anomalies. Here we present results from an experiment conducted during the 2014 bleaching event in the Florida Keys, USA, that exposed Agaricia sp. (Undaria) and Siderastrea siderea corals to 3 types of elevated nutrients: nitrogen alone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 71 publications
(92 reference statements)
5
48
1
Order By: Relevance
“…In other words, nutrient levels, or UVR exposure, did not increase the severity of bleaching above back ground levels, because temperature had a large impact alone. Two other studies, which have analysed the bleaching severity at different distances from nutrient sources, found no significant impact of nutrient levels on bleaching, in agreement with our observations [ 3 , 52 ]. It was however observed that high nutrient levels did, to some degree, prolonged bleaching in some coral species, and had a distinct effect on coral microbiomes that was independent of temperature [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In other words, nutrient levels, or UVR exposure, did not increase the severity of bleaching above back ground levels, because temperature had a large impact alone. Two other studies, which have analysed the bleaching severity at different distances from nutrient sources, found no significant impact of nutrient levels on bleaching, in agreement with our observations [ 3 , 52 ]. It was however observed that high nutrient levels did, to some degree, prolonged bleaching in some coral species, and had a distinct effect on coral microbiomes that was independent of temperature [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…Two other studies, which have analysed the bleaching severity at different distances from nutrient sources, found no significant impact of nutrient levels on bleaching, in agreement with our observations [ 3 , 52 ]. It was however observed that high nutrient levels did, to some degree, prolonged bleaching in some coral species, and had a distinct effect on coral microbiomes that was independent of temperature [ 52 ]. Many other studies have linked seawater eutrophication with a higher bleaching susceptibility of different coral species [ 11 , 53 , 54 , 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…A total of 10 fungi orders, 25 genera, and 23 species were found to be specific for S. siderea (Supplementary Figure S2). The eukaryotic communities identified in this study were limited to Ascomycota (97.41%) and Basidiomycota (2.26%) groups, in contrast to previous studies in which Microsporidia, Chytridiomycota, and Entomophthoromycota were detected as the most abundant phyla within the coral microbiome (Wang et al, 2018). Among the observed classes, Dothideomycetes (55.44%) and Sordariomycetes (18.13%) were the predominant classes but unlike other samples, Orbiliomycetes (0.47%) and Lecanoromycetes (0.08%) were also identified in association with this host.…”
Section: Eukaryotic Community Composition Associated With Siderastreacontrasting
confidence: 99%
“…1). Coral bacterial communities are altered by changing environmental conditions such as pollution [17,74], nutrient availability [17,75], environmental anomalies such as temperature [16,21,76], salinity [28], pH [77,78], and eutrophication [79]. Such compositional flexibility indicates a potential capacity for local acclimatization (or adaptation), and thus may be critical for promoting holobiont fitness a.…”
Section: Bacterial Community Plasticity Across Sitesmentioning
confidence: 99%